2016
DOI: 10.1016/j.pbb.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine administration at night during extended wakefulness effectively mitigates performance impairment but not subjective assessments of fatigue and sleepiness

Abstract: The current study investigated the effects of repeated caffeine administration on performance and subjective reports of sleepiness and fatigue during 50h extended wakefulness. Twenty-four, non-smokers aged 22.5±2.9y (mean±SD) remained awake for two nights (50h) in a controlled laboratory environment. During this period, 200mg of caffeine or placebo gum was administered at 01:00, 03:00, 05:00 and 07:00 on both nights (total of 800mg/night). Neurobehavioral performance and subjective reports were assessed throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Participants were recruited to take part in a study investigating the effects of caffeine gum administration on performance and sleepiness during 50 h of total sleep deprivation (TSD). Data pertaining to the scope of the larger study are published elsewhere (Johnson et al, 2016;Paech et al, 2016). Only data relating to the control condition (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were recruited to take part in a study investigating the effects of caffeine gum administration on performance and sleepiness during 50 h of total sleep deprivation (TSD). Data pertaining to the scope of the larger study are published elsewhere (Johnson et al, 2016;Paech et al, 2016). Only data relating to the control condition (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, self-assessment of sleepiness or performance during extended wakefulness is the most common method of monitoring performance and safety in the workplace (Christodoulou, 2012). However, inter-individual differences in the effects of sleep loss on performance (Van Dongen et al, 2004) and reports of discrepancies between subjective assessment of sleepiness and objective performance (Paech et al, 2016;Zhou et al, 2012), have led to the recent interest in non-invasive, objective, physiological monitoring of operator performance.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the stimulant function of caffeine, it stimulates the central nervous system and cardiac activities (Seifert et al, 2011;Trabulo et al, 2011), increasing the physical anbd mental performance, improving the sense of humor and memory (Bizzotto et al, 2013;Malinauskas et al, 2007;Pohler, 2010). Paech et al (2016) administered caffeine to adults who were kept awake for 50 hours; the results showed that the individuals who received caffeine presented a lower reduction of performance when compared with the control group; however, they did not observe any reduction in the sensation of sleep and tiredness.…”
Section: Introductionmentioning
confidence: 99%
“…Participants then began 50 hr of extended wake (day 1; 08:00 hours to day 3; 10:00 hours, <50 lux). Throughout the extended wake period, participants completed cognitive test batteries at regular intervals, results published elsewhere (Johnson et al., ; Paech, Banks et al., ; Pajcin et al., ). Meal tolerance tests were completed at breakfast on days 2–4.…”
Section: Methodsmentioning
confidence: 99%